O patrimônio azulejar de São Luís - MA e a relação das pessoas com os produtos inspirados nos objetos culturais - SILVA, Keity Lílian Barbosa Martins (2021)
The artifacts constituting a historical heritage refer to objects made in other times, preserved fundamentally because of their historical, cultural and symbolic value (LEMOS, 2017; MENESES, 2004). In addition to these attributes, they communicate through their aesthetic and structural characteristics, such as styles, shapes, materials, symbols, colors, ornaments and compositions (CARDOSO, 2016; DONDIS, 2015; NIEMEYER, 2016). Therefore, this research aims to contribute to the area of design in the field of cognitive ergonomics, which deals with mental and emotional processes in the relationship of people with objects (FALZON, 2007; NORMAN, 2006, 2008). The main objective of the investigation was to analyze the perception of residents in São Luís - MA about the tile heritage of the city in order to understand how it affects the relationship of people with products inspired by historic tiles. For this, the research was supported by interdisciplinary theoretical concepts covering the areas of cognitive ergonomics, visual perception, aesthetics, semiotics, historical heritage and tile heritage, in order to offer a holistic view on the perception of historical artifacts and interaction with the products. As for the nature of the data, the research is mixed - quantitative and qualitative (CRESWELL, 2010), at a descriptive level (GIL, 2019). The research method selected is a case study (YIN, 2015), with the historical-cultural artifacts to be analyzed in the relation of perception, the tiles of the São Luís - MA tile heritage. And as a result of the research, we infer that the visualization of artifacts from a historical heritage incites in the subjects a repertoire of memories, feelings and sensations leading them to a context of nostalgia, nostalgia, memories and even indifference, depending on the relationship established with the objects. Also, we emphasize that the affinity of people with historical tiles is fundamentally in the aesthetic and symbolic spheres. And that the memories, feelings and sensations experienced by the subjects in the interaction with products alluding to a historical heritage are, therefore, similar to those experienced in the context of the heritage itself. They are, in fact, projections and updates from people (FREUD, 1985 apud LAPLANCHE; PONTALIS, 1986) evidenced in the products. In this sense, there is, therefore, a desire for historical perpetuation and personal satisfaction, even if unconscious, which affects identification with representative signs and symbols in an affective sphere. We also evidence that the products are embedded with meanings and qualities and that their different categories carry in their materiality a set of associations and symbologies. In this sense, we identified that the ceramic tiles and trays with the tile theme convey the idea of traditionalism, durability, communion and attachment, referring to a historical scenario. However, cans and key chains are considered more ephemeral and detached from feelings of affection. And sandals were pointed out as not consistent with the theme of historic tiles. Choosing floors and coverings, since they are building materials for long-term use, depends on factors such as: economic value, the need for a particular environment and the consumer's style. The use of this theme in products was, finally, identified as strategic, relevant and necessary for the promotion of heritage.